The species of Acylophorus Nordmann (Coleoptera: Staphylinidae: Staphylininae) in continental sub-Saharan Africa - Lott, Derek A. (Zootaxa, 2010)
Types of Acylophorus delphinus Fauvel from Madagascar and Acylophorus species found in continental sub-Saharan Africa are revised. Lectotypes are designated for the following species: A. orientalis Fauvel, A. picipennis Bernhauer, A. densipennis Bernhauer, A. antennalis Cameron, A. tenuiceps Bernhauer, A. collarti Cameron, A. congoensis Cameron, A. mareei Bernhauer, A. trigonocephalus Cameron and A. grandis Bernhauer. Type material for A. rufipennis Cameron could not be located and the name is considered to be a nomen dubium. The following new synonymies are established: A. orientalis Fauvel = A. picipennis Bernhauer syn. n., = A. marginalis Cameron syn. n.; A. antennalis Cameron = A. tenuiceps Bernhauer syn. n.; A. trigonocephalus Cameron = A. lomaensis Bordoni syn. n. Seven new species are described: A. nitens sp. n. from Sudan, A. tshuapensis sp. n. from Congo, A. makhoreae sp. n. from Ethiopia, A. micans sp. n. from Côte d’Ivoire and Gabon, A. salifi sp. n. from Burkina Faso, A. minor sp. n. from Côte d’Ivoire and Nigeria, and A. setiger sp. n. from Bioko (Equatorial Guinea). A key is given to species groups defined by easily observed characters. Comparative diagnoses are given for species, their distributions mapped and their bionomics detailed where data are available. Forebodies, terminal segments of the maxillary palpi, antennae and aedeagi are figured for all species, except those represented by material with these parts missing. Mandibles and secondary sexual characters are figured for selected species.